On the role of legal education of non-professional participants of criminal proceedings in the criminal science - Zubenko, Evgenii Vladimirovich; Bugaev, Evgenii Nikolaevich; Garmaeva, Darima Andreevna (Полицейская и следственная деятельность, 2021)
The research subject is the activity of public authorities and officials related to anti-criminal education of non-professional participants of criminal proceedings, and the legal regulation of such an activity within a criminal investigation. The authors study the role of legal awareness in criminal science. The research object is social relations regulating the activity at the level of public authorities and their officials aimed at legal education. The authors consider legal education as a part of an investigator's work, which should be reflected in criminal science. The research methodology is based on the dialectical and formal-legal research methods, as well as the analysis of regulatory documents and criminalistic literature. The authors describe the role of legal education (in the course of their formation) within the structure of criminal science. It can be implemented within one or several tactical methods (their combination); as a general provision of the criminal investigation technique; as a subtheory of criminal science.